Baduanjin’s impact on quality of life and sleep quality in breast cancer survivors receiving aromatase inhibitor therapy: a randomized controlled trial - Liao, Jingwen; Chen, Yanyu; Cai, Li; Wang, Kun; Wu, Shenghui; Wu, Lan; Song, Bixiao; Hu, Min; Hou, Xiaohui (Frontiers in Oncology, 2022)
Purpose: The aim of the current study is to investigate the impact of Baduanjin, a traditional Chinese exercise, on quality of life and sleep quality in breast cancer survivors receiving aromatase inhibitors (AIs) therapy. Methods: A total of 72 breast cancer survivors who had received AI treatment for more than 6 months were enrolled in the current study using non-probability consecutive sampling procedure. Participants were randomly assigned in a 1:1 ration to 12-week Baduanjin exercise programmeclass or to a wait-list control group. The Baduanjin exercise group performed two 90-minute supervised sessions per week. The primary outcomes were changes in quality of life measured by the European Organization for Research and Treatment of Cancer Quality-of-Life Questionnaire Core 30 (EORTC QLQ-C30) and in sleep quality evaluated using the Pittsburgh Sleep Quality Index (PSQI). Results: A total of 68 participants completed the trial (Baduanjin exercise group: n=33; control group: n=35). Baseline values for quality of life did not differ between groups. Both global quality of life and physical functioning score increased significantly by 12.39 (P<0.001) and 8.48 (P<0.001) in Baduanjin exercise group compared with the control. Overall PSQI score also decreased by 4.85 (P<0.001) in Baduanjin exercise group, whereas it increased by 0.34 in the control group. Conclusion: Baduanjin exercise training led to improvement in the quality of life and sleep quality of breast cancer patients undergoing AI therapy.